Phytoremediation of arsenic-contaminated waters by artificial floating island: Literature review - Fonseca, Kalina (2020)
Water is the main way arsenic (As) can ge tinto the human body causing irreversible health damage such as poisoning, skin lesions and various types of cancer. One strategy for addressing pollution of arsenic in aquatic ecosystems is artificial floating islands (IFA) using Vetiver grass (Chrysopogon zizanioides). The objective of this study was to review 45 publications on the fundamentals of construction, implementation, description of decontamination mechanisms, characterization of macrophyte species and final disposal of plant material. Also, some mathematical models that can be applied to quantify removal rates and system efficiency were reviewed. Based on the literature reviewed, it is concluded that Vetiver grass is an effective alternative in removing As and its effect can be amplified by implementing an artificial floating bed. The importance of this relatively new ecotechnology requires further research in the field.